2020
DOI: 10.17645/up.v5i2.2940
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmanalysis of Urban Events: Empirical Elements from the Montreux Jazz Festival

Abstract: This article proposes an original approach to urban events mapping. At the theoretical level, the article is based on rhythmanalysis and recent research on urban rhythms. It contrasts with previous research by departing from everyday rhythms to tackle the specific rhythms of urban events. Drawing on this theoretical framework, the article proposes to analyse the rhythms of the Montreux Jazz Festival. The article proposes two main types of rhythmic scales, linked with the historical development of the Festival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…Étant donné la diversité des domaines de recherche et des objets, certains auteurs considèrent que ces ensembles de réflexions re lativement hétérogènes demandent à être intégrés dans une science gé nérale des processus de territorialisation et de socialisation en mettant en perspective les mélodies et les refrains des territoires et des relations so ciales (Brighenti et Kärrholm 2018). En touchant notamment aux domaines de l'aménagement du territoire, le rythme apparaît également comme un levier de régulation des pressions sur les environnements na turels, les milieux urbains (Drevon et al 2020a) et permettrait également de réduire les différentes formes de saturations présentes dans nos vies et dans nos villes .…”
Section: Plaidoyer Pour Une Rythmologie Des Sociétés Contemporainesunclassified
“…Étant donné la diversité des domaines de recherche et des objets, certains auteurs considèrent que ces ensembles de réflexions re lativement hétérogènes demandent à être intégrés dans une science gé nérale des processus de territorialisation et de socialisation en mettant en perspective les mélodies et les refrains des territoires et des relations so ciales (Brighenti et Kärrholm 2018). En touchant notamment aux domaines de l'aménagement du territoire, le rythme apparaît également comme un levier de régulation des pressions sur les environnements na turels, les milieux urbains (Drevon et al 2020a) et permettrait également de réduire les différentes formes de saturations présentes dans nos vies et dans nos villes .…”
Section: Plaidoyer Pour Une Rythmologie Des Sociétés Contemporainesunclassified
“…Their examination of the activity rhythms showed that a street classification framework based on temporal street activity patterns can identify street categories at a finer granularity than other current methods, which can offer useful implications for state-of-the-art urban management and planning. Furthermore, in their study, Drevon et al [39] addressed the rhythm-analytic approach to large urban events in order to confirm the impact of the event program and its structure on flows, oscillations between high-and low-intensity periods and the effects of the wider organisation of the leisure system. The circadian visualisation reveals the spread, which shows how the festival is integrated into the existing urban fabric, the openness, which shows accessibility, and the grip, which seeks to evaluate the wider influence of the event enriched by the addition of other data, including ticket scanning and commercial transactions.…”
Section: Analysis Of Urban Rhythmsmentioning
confidence: 99%
“…It has been determined that various processes in our cities follow rhythmical patterns, and thus detailed analysis of rhythmicity (on a daily basis, weekly basis, seasonally, etc.) can extend the excavation of efficiency metrics, which depend on different factors (e.g., type of day (weekend or workday), weather conditions and time of year) and represent an important step in research supporting data-driven urban planning, responsive policies and management [37,39,41]. We should further extend these with the application of the proposed research in various monitoring scopes, from resource efficiency and sustainability to dwelling quality within smart city environments, with inputs ranging from vehicle count sensors, emissions and noise sensors, pedestrian sensing or passenger counts to other open repositories of governments or municipalities (e.g., energy consumption indicators or city overheating data or patterns) or citizen science-based infrastructures and their wider applicability.…”
Section: Analysis Of Urban Rhythmsmentioning
confidence: 99%